2017
DOI: 10.1007/s12011-017-1003-5
|View full text |Cite
|
Sign up to set email alerts
|

Serum Hepcidin and Soluble Transferrin Receptor in the Assessment of Iron Metabolism in Children on a Vegetarian Diet

Abstract: The aim of this study was to assess the effect of vegetarian diet on iron metabolism parameters paying special attention to serum hepcidin and soluble transferrin receptor (sTfR) concentrations in 43 prepubertal children (age range 4.5–9.0 years) on vegetarian and in 46 children on omnivorous diets. There were no significant differences according to age, weight, height, and body mass index (BMI) between vegetarian and omnivorous children. Vegetarians had similar intake of iron and vitamin B12 and a significant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
46
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(50 citation statements)
references
References 41 publications
1
46
0
3
Order By: Relevance
“…(d) evaluation of suspected iron overload disorders 13 ; (e) evaluation of ID, before the occurrence of iron deficiency anemia (IDA), for example in pregnant women, 14,15 in children, 16,17 and in children with cystic fibrosis. 18 Apart from diagnostic applications, multiple agents targeting the hepcidin/ferroportin axis are under development as novel therapeutics for iron disorders in adults.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…(d) evaluation of suspected iron overload disorders 13 ; (e) evaluation of ID, before the occurrence of iron deficiency anemia (IDA), for example in pregnant women, 14,15 in children, 16,17 and in children with cystic fibrosis. 18 Apart from diagnostic applications, multiple agents targeting the hepcidin/ferroportin axis are under development as novel therapeutics for iron disorders in adults.…”
Section: Introductionmentioning
confidence: 99%
“…[24][25][26] Available studies concern either small series with limited age groups or series including children with (anemia of) inflammation. 16,[27][28][29][30][31] As a first step to the implementation of serum hepcidin measurements in pediatric clinical practice, we established age-and sex-specific (Table 1).…”
Section: Introductionmentioning
confidence: 99%
“…Кроме того, рацион вегетарианцев часто дефицитен по содержанию железа, цинка и йода [10][11][12]. Частота дефицита железа, выявляемая по уровню железа, и сниженного уровня ферритина и гепцидина в сыворотке крови среди детей-вегетарианцев 2-18 лет обнаруживается чаще, чем среди невегетарианцев того же возраста [13,14]. Низкий статус железа у детей-вегетарианцев может приводить к снижению уровня иммуноглобулинов IgA, IgM и IgG в сыворотке крови [15].…”
Section: оригинальные статьиunclassified
“…Это не вызывает удивления, поскольку обычно рацион вегетарианцев содержит значительное количество свежих овощей и фруктов. В результате потребление витамина С, как правило, превышает таковое у детей, получающих смешанный рацион [6,14].…”
Section: результаты и обсуждениеunclassified
“…sTfR is commonly used for the clinical determination of iron status, which is less affected by inflammation. Although recent data showed that serum ferritin levels were positively and independently associated with insulin resistance (IR) [13], Ambroszkiewicz J et al [15] found that soluble transferrin receptor, which was less affected by inflammation, was a better marker of iron status than other parameters.Many previous studies have shown that iron metabolism disorder may contribute to the pathogenesis of GDM. However, the correlation between iron metabolism and GDM is not well known.…”
Section: Introductionmentioning
confidence: 99%